2019
DOI: 10.1073/pnas.1908355116
|View full text |Cite
|
Sign up to set email alerts
|

RIP1 kinase mediates angiogenesis by modulating macrophages in experimental neovascularization

Abstract: Inflammation plays an important role in pathological angiogenesis. Receptor-interacting protein 1 (RIP1) is highly expressed in inflammatory cells and is known to play an important role in the regulation of apoptosis, necroptosis, and inflammation; however, a comprehensive description of its role in angiogenesis remains elusive. Here, we show that RIP1 is abundantly expressed in infiltrating macrophages during angiogenesis, and genetic or pharmacological inhibition of RIP1 kinase activity using kinase-inactive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 72 publications
(94 reference statements)
3
23
0
Order By: Relevance
“…Recently, Ueta et al demonstrated that in pathological angiogenesis mouse model, RIPK1 abundantly expresses in infiltrating macrophages and inhibition of RIPK1 alleviates angiogenesis. Furthermore, caspase inhibition can augment RIPK1 activation, which cause aggravation of pathological angiogenesis [54]. Similarly, during the study, we found that 100 µM Z-IETD-fmk treatment decreases the activity of caspase-8 but aggravates CNV comparing with the 40 µM group.…”
Section: Discussionsupporting
confidence: 63%
“…Recently, Ueta et al demonstrated that in pathological angiogenesis mouse model, RIPK1 abundantly expresses in infiltrating macrophages and inhibition of RIPK1 alleviates angiogenesis. Furthermore, caspase inhibition can augment RIPK1 activation, which cause aggravation of pathological angiogenesis [54]. Similarly, during the study, we found that 100 µM Z-IETD-fmk treatment decreases the activity of caspase-8 but aggravates CNV comparing with the 40 µM group.…”
Section: Discussionsupporting
confidence: 63%
“… 23 Therefore, M2 macrophage infiltration in CNV lesions is an emerging target for CNV therapy. 24 , 25 In our study, activation of the p300/XBP1s/Herpud1 axis in infiltrating M2 macrophages promoted the proliferation, migration and tube formation of choroidal endothelial cells. Furthermore, blockade of the p300/XBP1s/Herpud1 axis inhibited the M2 polarization of macrophages and alleviated the development of CNV, in consistent with previous studies.…”
Section: Discussionsupporting
confidence: 55%
“…Infiltrating macrophages interact with choroidal endothelial cells through Notch receptor 1 (Notch1) signalling during retinal sprouting angiogenesis 23 . Therefore, M2 macrophage infiltration in CNV lesions is an emerging target for CNV therapy 24,25 . In our study, activation of the p300/XBP1s/Herpud1 axis in infiltrating M2 macrophages promoted the proliferation, migration and tube formation of choroidal endothelial cells.…”
Section: Discussionmentioning
confidence: 65%
“…Washed 4 times for 3 minutes each in TBST and then incubated with secondary HRP-conjugated antibodies accordingly for 25 minutes at room temperature before final washing step, 4 times for 3 minutes each. Membranes were developed using chemiluminescent substrate (ECL Select western blotting detection reagent, RPN 2235, GE Healthcare Life Sciences, USA) [ 87 ] and images captured by using the ChemiDoc imaging system (Bio-Rad, Hercules, CA, USA). For full list of the antibodies used see S1 Table .…”
Section: Methodsmentioning
confidence: 99%